S7 Adiposity and asthma, pulmonary function and atopy in 11-year old children: a birth cohort study. (2nd December 2011) - Wang, R; Custovic, A; Simpson, A; Lowe, L; Murray, C S
Abstract : Background: Results of studies investigating the association between obesity and asthma, atopy and lung function have been inconsistent, in part due to the limitation of BMI in evaluating body adiposity. Objectives: To investigate the association between obesity and asthma, wheeze, atopy, lung function and bronchial hyper-responsiveness in children at age 11 years using bioelectrical impedance (BIA) and BMI. Methods: Children from the unselected birth cohort study attending follow-up at age 11 years had percent body fat (PBF) and truncal fat (PTF) assessed using BIA (Tanita BC-418). Weight and height were also measured. Current asthma and wheeze were derived from a validated respiratory questionnaire. Atopy was ascertained using skin prick testing. Lung function was assessed using spirometry and bronchial hyper-responsiveness by 5-step methacholine challenge according to ATS guidelines. Results: 646 children (339 male) completed anthropometric measurements. BMI z-score, PBF and PTF were associated with current wheeze (OR [95% CI]: 1.27 [1.03 to 1.57], p=0.03; 1.04 [1.00, 1.08], p=0.04; 1.04 [1.00, 1.08], p=0.04 respectively). BMI z-score, PBF and PTF were also associated with current asthma (1.30 [1.04 to 1.63], p=0.02; 1.04 [1.00 to 1.08], p=0.06; 1.04 [1.00 to 1.08], p=0.04). However, the effect of PBF and PTF appeared strongest in girls (PBF: 1.12 [1.04 to 1.20], p=0.004; PFT: 1.11[1.04 to 1.20], p=0.003; p=0.05 and p=0.04 for interactions respectively). Children were defined as normal or overweight according to BMI (23% overweight) and PBF (29.8% overweight) cut-offs; overweight children had an increased risk of asthma (BMI: 1.73 [0.99 to 3.02], p=0.05; PBF: 2.09 [1.23 to 3.32] p=0.006). This was highly significant in girls (BMI: 3.34 [1.43 to 7.83], p=0.005; PBF: 4.74 [1.98 to 11.35], p<0.001; p=0.05 and p=0.02 for interactions respectively). Increasing BMI was associated with increases in both FEV1 and FVC but reductions in FEV1 : FVC ratios. This association was again stronger in girls than boys. No associations between adiposity and atopy or bronchial hyper-responsiveness were found. Conclusion: Higher BMI z-score, PBF and PTF were associated with increased risks of wheeze and asthma. This effect was stronger in girls. BIA measurements appeared to have stronger associations in girls with outcomes than BMI. This may reflect the ability of BIA to measure adiposity more accurately than BMI.